Incremental Short Text Summarization on Feedback in Real Time from Social Community Services - Mounika, S.; Yasan, Srinadh (International Journal For Research In Advanced Computer Science And Engineering, 2016)
In this paper, We mainly focuses on comments which has been posted in social sites like facebook, twitter etc. This is mainly used to improve the quality of comments by grouping comments with similar content together and generate a concise opinion summary for this message. In this we are using a IncreSTS algorithm that update clustering results with latest incoming comments in real time. Therefore,We design an at-a-glance visualization interface that help the users to identify the comments easily and rapidly get an overview of the summary.From this experimental results,We possesses the advantages of high efficiency, high scalability,and better handling outliers, which justifies the practicability of IncreSTS on the target problem.